Land Conservation and Pest Management of Agriculture Perspective Islamic Religion - Gunawan Ikhtiono; Bahagia Bahagia; Rimun Wibowo; Fachruddin Majeri Mangunjaya (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
Abstract The aim of this research will investigate numerous aspects including agriculture sustainability from an Islamic perspective. The method used is a literature review with descriptive analysis. The result is Islam has several actions to reach farming base on the environment such as the barring of killing some of the animals comprise frog, eagle, bee, and other animal which is valuable for creating ecosystem balance. The action is integrating pest mitigation by way of using nature power to decline the population of insect attacks. The other is to rekindle of land is the most imperative action to assert sustainable agriculture. Lands must be cultivated as people mandatory to God’s but don’t create killing and vanishing of an animal which bolster soil fertility. For this, the land has to preserve through organic manure to attaint Ihya-Almawat or planting land without ravage soil. The impact is climate change can be encouraged. Then, people who cultivate seed or plant to land, the person will receive a reward from God. While planting plant produces alms as capital for a person when they confront God’s. As result, the people on earth obtain some merits such as people get oxygen, shading, habitat for the animal, and save a life from the unpredicted climate.Keywords: Agriculture, Climate, Environment, Islam Abstract Penelitian ini bertujuan untuk mengkaji berbagai aspek termasuk pertanian berkelanjutan dalam perspektif Islam. Metode penelitian yang digunakan adalah pendekatan literature review dengan descriptif analisis. Ada beberapa hasil dari penelitian ini yaitu ajaran Islam memiliki beberapa tindakan untuk mencapai pertanian ramah alam mulai dari larangan membunuh katak, elang, dan lebah untuk menciptakan keseimbangan ekosistem. Warisan ajaran ini mengintegrasikan pengendalian hama dengan kekuatan alam. Warisan jaran yang lain yaitu menghidupkan lahan agar lahan tetap produktif dan berkelanjutan. Tanah harus diolah sebagai namun tidak menciptakan pembunuhan dan pemusnahan hewan yang menyebabkan tanah menjadi gersang. Untuk itu, tanah harus diawetkan melalui pupuk organik untuk mencapai Ihya-Almawat atau tanah tanam tanpa merusak tanah. Kemudian, orang yang membudidayakan tanaman akan menerima pahala berupa sedekah. Terdapat beberapa sedekah seperti makhluk hidup mendapatkan oksigen, bisa berteduh, menjadi habitat hewan, dan menyelamatkan kehidupan dari iklim yang tidak terduga.Keywords: Pertanian, Iklim, Lingkungan, Warisan Islam